The impact of country connectedness and cultural values on the equity of a country's workforce. Issue 1 (2nd February 2015) - DesAutels, Philip; Berthon, Pierre; Caruana, Albert; Pitt, Leyland F.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to focus on the impact that country connectedness and cultural values have on the equity afforded to a country's workforce in today's global economy. Design/methodology/approach – Drawing upon a number of large international surveys of national-level metrics, e-readiness is identified as a proxy measure for country connectedness. Cultural variables are proxied by the World Values Survey's national-level scores on "survival/self-expression" and "traditional/secular-rational" values. Workforce equity is captured via three measures: per capita Gross National Income (GNI) based on purchasing power parity (PPP), a Gini-coefficient, and the prevalence of child labor. Stepwise regression analysis is employed to investigate expected relationships. Findings – Results suggest an interesting link between the constructs investigated. A negative and significant effect of e-readiness and a negative and significant effect of traditional/secular-rational values on workforce equity are reported. In addition, the impact of e-readiness appears to be absolutely larger while thee impact of survival/self-expression values on the workforce equity is not found to be significant. Research limitations/implications – The research is primarily exploratory in nature thereby providing a foundation but not an end product. Next, the data used in the research is aggregate-level data providing broad generalizations about each country. Does a country have a single culture? Is the connectivity of a country a valid measure of the regions within? The authors chose to use an analysis at a single point in time. A longitudinal study could provide more insight and thus help to highlight causality. The data utilized was repurposed from third-party sources. Finally, only 37 observations are used and a broader data set could help strengthen findings further. Social implications – The rapid march of country connectedness across the globe is eroding firms' ability to shade their actions through the distance afforded by global supply chains. A country's culture values has a significant impact on workforce equity but country connectedness has a stronger impact, thus companies operating in more traditional and less developed countries will face significant impacts as these countries get connected. Rather than a threat, companies may see country connectedness and workforce equity as an opportunity. Firms that treat their workers well will see vast new markets open for them as evermore of the world's population becomes economically active. Originality/value – Uses an innovative data capture methodology that allows the investigation of an interesting and unexplored research question.